A portrait of Emily Price [large type] - Reay, Katherine, 1970- (Center Point Large Print, 2017)
"Art restorer Emily Price has never encountered anything she can't fix--until she meets Ben, an Italian chef, who seems just right. When Emily follows Ben home to Italy, she learns that his family, however, is another matter"--